Rancang Bangun Sistem Informasi Alih Media dan Retensi Dokumen Rekam Medis Berbasis Web di RS Widodo Ngawi - Mubarot Isa; Mudafiq Riyan Pratama; Mochammad Choirur Roziqin; Dony Setiawan Hendyca Putra (Indonesian Journal Publisher, 2026)
Widodo Ngawi Hospital is currently handling the high volume of medical record documents, with 11,986 outpatient documents and 13,065 inpatient documents in 2023. Retention activities have not been carried out since 2015 due to the unavailability of a system that supports transferring medical record documents and retention alerts. The absence of retention activities has reduced the storage capacity of medical record documents, resulting in medical record documents being easily damaged, not neatly arranged, and not in accordance with their preparation, causing services to patients to be less optimal and efficient. The purpose of this study is to design and create a web-based medical record document transfer and retention information system to support media transfer and retention of medical record documents. The method used is the Waterfall system development method, which consists of needs analysis, design, code generation, testing, and maintenance, though the maintenance stage is not carried out in this study. The result of this research is an information system that helps media transfer, retention, and destruction. Based on the test results, the system functions properly, and no errors were found in all modules on both admin and user access rights.